ANALYSING BARRACK OBAMA’S CAIRO SPEECH ‘A NEW BEGINNING’ (A STUDY OF CRITICAL DISCOURSE ANALYSIS [CDA]) - Syarifuddin Syarifuddin (Universitas Yudharta Pasuruan, 2017)
This essay will analyse and discuss Barrack Obama’s Cairo speech by using CDA framework such as lexical sets and choice of lexis, modality, cohesion and coherence, and generic structure of text. Based on the analysis and discussion, the choice of lexis may give an impact on the way the listeners think and believe to what Obama says, to show to the listeners that Obama understands the religion of his audience, to show his seriousness of making ‘a new beginning’ with Muslims around the world, to give a good impression of the overall of the speech to the audience, and to appreciate Muslim audience. In cohesion and coherence, it is well organized which means Obama tries to make his speech easier to follow by everyone by using additive conjunctions’ or ‘transition phrases’ which have a function ‘to list in order’. Besides, the generic structure of the speech is well structured.